Social Criticism in "Eye of the Storm" Album by One Ok Rock - nurul faizah; dian mukhlisa; Firdiansyah Firdiansyah (English Language, Linguistics, Literature, And Education Journal, 2022)
This research is focused on social criticism in Eye of the Storm Album by One Ok Rock. The purpose of this research is to know the problems of social criticism in “Eye of the Storm” Album by One Ok Rock and the forms of of social criticism in “Eye of the Storm” Album by One Ok Rock . This research method is a qualitative method and the technique of the research is descriptive analysis to analyze the data with theory that related to the problem of the writer’s research. The data are collected from lyrics in the songs. The finding shows that there are three problems of social criticism which are social criticism in youth of modern society problem contained in the song lyrics with the title Stand Out Fit In, Giants, and Head High, social criticism in environment problem contained in the song lyrics with the title Stand Out Fit In, Change, Head High, and Giants. Then social criticism in bureaucracy problem contained in the song lyric with the title Push Back. While, there are three forms of social criticism which are unadorned criticism, symbol criticism, and cynical criticism.